2016
DOI: 10.1162/edfp_a_00176
|View full text |Cite
|
Sign up to set email alerts
|

Playing to Teachers’ Strengths: Using Multiple Measures of Teacher Effectiveness to Improve Teacher Assignments

Abstract: Current uses of value-added modeling largely ignore or assume away the potential for teachers to be more effective with one type of student than another or in one subject than another. This paper explores the stability of value-added measures across different subgroups and subjects using administrative data from a large urban school district. For elementary school teachers, effectiveness measures are highly stable across subgroups, with correlations upwards of 0.9. The estimated cross-subject correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…A more specific concern about measurement is that individual teachers might provide different kinds of learning opportunities to different types of students, leading overall effectiveness to be an imperfect proxy for students’ experiences. 7 Evidence on this possibility is mixed— student-teacher match effects (based on race or gender) suggest some differences exist (Dee 2004; Gershenson, Holt, and Papageorge 2016), while teacher effectiveness measures show little heterogeneity by student characteristics (Condie et al 2014; Fox 2015)— but even small differences could influence conclusions about the current research questions. To consider how such heterogeneity (including but not limited to teacher characteristics), I relax the assumption of homogeneous teacher effects by calculating subgroup-specific effectiveness estimates by economic disadvantage and for Black and White students.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more specific concern about measurement is that individual teachers might provide different kinds of learning opportunities to different types of students, leading overall effectiveness to be an imperfect proxy for students’ experiences. 7 Evidence on this possibility is mixed— student-teacher match effects (based on race or gender) suggest some differences exist (Dee 2004; Gershenson, Holt, and Papageorge 2016), while teacher effectiveness measures show little heterogeneity by student characteristics (Condie et al 2014; Fox 2015)— but even small differences could influence conclusions about the current research questions. To consider how such heterogeneity (including but not limited to teacher characteristics), I relax the assumption of homogeneous teacher effects by calculating subgroup-specific effectiveness estimates by economic disadvantage and for Black and White students.…”
Section: Methodsmentioning
confidence: 99%
“…Clotfelter and colleagues (2006) find a similar pattern-larger benefits for nonpoor students and students whose parents have more education-for assignment to an experienced teacher among fifth-grade students in North Carolina. Studies also report evidence that teacher effects are highly correlated across different types of students (e.g., Condie, Lefgren, and Sims 2014;Fox 2015); this work suggests that teachers' relative ranking is similar across groups, but these studies do not directly assess the magnitude of differential benefits that students experience. Existing evidence suggests that differences in teacher effects are likely to be small relative to teachers' overall effects, but prior work is ambiguous about the direction and precise size of consequential compounding or compensatory influences.…”
Section: Teachers Differential Benefits and Inequalitymentioning
confidence: 97%
See 1 more Smart Citation
“…Xu, Özek, and Hansen (2015) found that improvements in the effectiveness of new teachers was related more to initial effectiveness than school poverty, suggesting that it may not be harder to learn to teach effectively in high-poverty schools. Fox (2016) found minimal differential effectiveness within teachers by student ability or free lunch status, suggesting teachers may not find it more difficult to teach effectively with poor or lower-achieving students. There is also some evidence that classroom student achievement growth as measured by value added can actually be greater for students with lower prior achievement (e.g., Protik, Walsh, Resch, Isenberg, & Kopa, 2013), but it is unclear whether this is due to test ceilings or similar artifacts (Resch & Isenberg, 2014).…”
Section: Student Disadvantagementioning
confidence: 86%
“…To the degree that teachers are differentially effective in certain contexts (e.g., with different student populations or in different subjects or grade levels), there may be gains to be made by using value-added information to reorganize the existing workforce; teachers could be tasked with instructing students in subjects to which they are well matched given their skill sets. For example, Goldhaber and Cowan (2014) and Fox (in press) use findings on the value added of elementary teachers in math and reading instruction to examine the potential gains from teacher subject specialization. Both studies find that despite a high correlation in teacher effectiveness across math and reading, simulations suggest that subject specialization could lead to substantial gains in value added in math and small gains in reading.…”
Section: In What Ways Might Value Added Influence Teacher Quality?mentioning
confidence: 99%